2021
DOI: 10.1101/2021.10.03.21264320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humoral immune responses to COVID-19 vaccination in people living with HIV receiving suppressive antiretroviral therapy

Abstract: Background. Our understanding of COVID-19 vaccine immune responses in people living with HIV (PLWH) remains incomplete. Methods. We measured circulating antibodies against the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein and ACE2 displacement activities after one and two COVID-19 vaccine doses in 100 adult PLWH and 152 controls. Results. All PLWH were receiving suppressive antiretroviral therapy, with median CD4+ T-cell counts of 710 (IQR 525-935) cells/mm3. Median nadir CD4+ T-cell count… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 68 publications
9
23
0
Order By: Relevance
“…All the medians’ CD4 count was≥ 200 cells/µl (Supplementary material: Table 1). Sixteen studies reported the HIV viral load, among them, six studies included PLWH with viral load < 50 copies/ml [16, 45, 49, 51, 53, 54] and nine other studies included PLWH with viral load 58.1 to 95% suppressed [44, 46, 52, 55, 56, 58, 60, 61, 63, 65] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the medians’ CD4 count was≥ 200 cells/µl (Supplementary material: Table 1). Sixteen studies reported the HIV viral load, among them, six studies included PLWH with viral load < 50 copies/ml [16, 45, 49, 51, 53, 54] and nine other studies included PLWH with viral load 58.1 to 95% suppressed [44, 46, 52, 55, 56, 58, 60, 61, 63, 65] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selected articles reported data from United States of America (n = 4) [48–50, 55], China (n=5) [52, 54, 59, 61, 64], South Africa (n = 3) [45, 46, 57], United Kingdom (n = 2) [16, 53], Canada (n=2) [ 47, 51], Italia (n=1) [58], Brazil (n =1) [56], Germany (n =1) [60], Israel (n = 1) [44], Sweden (n=1) [64], Taiwan (n=1) [65] and Russia (n = 1) [62] ( Figure 2 ). Ten studies used randomized control designs [16, 45, 46, 49, 50, 53, 54, 64, 64, 65], eight studies used prospective cohort designs [44, 47, 48, 51, 52, 56–58], two retrospective cohort studies [62, 63], two cross sectional studies [59, 61] and one case control study [55] ( Supplementary material: Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations